SOMATOFORM AUTONOMIC DYSFUNCTION-A CASE REPORT - Savithaa (Journal of Health and Allied Sciences NU, 2013)
Somatoform disorders are characterized by a concern with the body and are among the most common reason for seeking medical help. Mr. X, a 47 year old male presented to the psychiatric department with persistent belching, fatigue and anxiety symptoms with autonomic arousal related to his work and health. Patient was treated with antipsychotics and cognitive behavioural therapy. Patient and family members were psycho educated about the illness.
Keywords: Somatoform disorders; somatoform autonomic dysfunction